Impact of road construction on tree diversity and forest structure in an intact Bornean mixed dipterocarp forest - Ideris, Nur; Jaafar, Salwana; Sukri, Rahayu (BRIN Publishing (Penerbit BRIN), 2025)
IDERIS, N. K. H, JAAFAR, S. MD. & SUKRI, R. S. 2025. Impact of road construction on tree diversity and forest structure in an intact Bornean mixed dipterocarp forest. Reinwardtia 24(1): 1–15. — Road construction has previously been shown to negatively impact biodiversity and is an urgent threat to Bornean tropical forests. We investigated changes in tree species diversity and forest structure of the Andulau Forest Reserve in Brunei Darussalam, following the construction of the Telisai-Lumut Highway. Within nine 20 × 20 m plots set up at varying distances from the forest edge where the road was located, we measured all trees ≥ 1 cm in diameter at breast height for their stem diameter, height and crown characteristics, and identified all trees ≥ 5 cm dbh. Although mean tree abundance and diversity between plots were similar, we detected significant differences in forest structure, particularly stem diameter, basal area, and crown characteristics. Plots closest to the road recorded the highest total tree species richness, although not significant, and contained a mixture of pioneer tree species and remnant interior forest species, while no pioneers were recorded in the interior forest plots. We documented the presence of high conservation value species, including three critically endangered species (Gonystylus bancanus, Hopea micrantha, and Vatica venulosa). Our work illustrates the potential impacts on forest structure from road construction and highlights the need for further studies to assess the long-term impacts on tree diversity and forest dynamics.